2008
DOI: 10.1186/1471-2180-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the new advanced 15-loci MIRU-VNTR genotyping tool in Mycobacterium tuberculosis molecular epidemiology studies

Abstract: Background: During the last few years, PCR-based methods have been developed to simplify and reduce the time required for genotyping Mycobacterium tuberculosis (MTB) by standard approaches based on IS6110-Restriction Fragment Length Polymorphism (RFLP). Of these, MIRU-12-VNTR (Mycobacterial interspersed repetitive units-variable number of tandem repeats) (MIRU-12) has been considered a good alternative. Nevertheless, some limitations and discrepancies with RFLP, which are minimized if the technique is compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 31 publications
3
51
1
5
Order By: Relevance
“…When we tolerated SLVs and compared the results from both techniques, identifying those isolates with more than 90% similarity in their RFLPs as clustered, the percentage of discrepancies fell from 14.6% to 8.6%. In addition, five of the remaining discrepancies involved a genotype belonging to the Haarlem lineage (identified with the code 28 in this study), which has been found to be markedly split by MIRU-VNTR analysis, suggesting that RFLP analysis is unable to offer enough discrimination to analyze with precision some of the isolates within this lineage (3,11,27,30,31,34). If we did not count cases involving these Haarlem strains, the number of discrepancies would fall to as low as 6.8%.…”
Section: Discussionmentioning
confidence: 99%
“…When we tolerated SLVs and compared the results from both techniques, identifying those isolates with more than 90% similarity in their RFLPs as clustered, the percentage of discrepancies fell from 14.6% to 8.6%. In addition, five of the remaining discrepancies involved a genotype belonging to the Haarlem lineage (identified with the code 28 in this study), which has been found to be markedly split by MIRU-VNTR analysis, suggesting that RFLP analysis is unable to offer enough discrimination to analyze with precision some of the isolates within this lineage (3,11,27,30,31,34). If we did not count cases involving these Haarlem strains, the number of discrepancies would fall to as low as 6.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Many efforts have been made to establish a reference method for a high-resolution genotyping of Mycobacterium tuberculosis strains (2,3,26,35) that could be used for epidemiological and phylogenetic studies and, recently, a standardized MIRU-VNTR set of 15 or 24 loci optionally combined with spoligotyping has been proposed (2). Fewer attempts have been made to find an optimized genotyping method for M. bovis and M. caprae strains, and probably the M. bovis populations in the different countries are too diverse to achieve a consensus set of markers useful in any situation.…”
Section: Discussionmentioning
confidence: 99%
“…A 24-locus format is more informative phylogenetically, and it can be used to trace transmission paths of TB (210,369,370). The discriminatory power of the 24-locus MIRU-VNTR typing system provides a resolution com-parable to that of IS6110-RFLP profiling (252,363,370,371). Therefore, 24-locus MIRU-VNTR typing has been suggested to be the new "gold standard" for molecular typing of MTBC strains.…”
Section: Methods Based On Repetitive Sequencesmentioning
confidence: 99%
“…Therefore, 12-locus MIRU-VNTR analysis was suggested to be used in combination with other genotyping methods (e.g., spoligotyping) to approximate the discriminatory power of IS6110 profiling (361,363). At the same time, 12-locus MIRU-VNTR analysis can be more discriminatory than IS6110-RFLP analysis if M. tuberculosis isolates with low copy numbers of IS6110 are under study (291-293, 364, 365).…”
Section: Methods Based On Repetitive Sequencesmentioning
confidence: 99%